P-098 Male age does not affect sperm motility rate after thawing and laboratory outcomes of transnational oocyte donation programs. (30th June 2022) - Scarica, C; Pontemezzo, E; Admitable, C; Bologna, F; Bosio, Y; Fasano, E; Gregori, O; Manniello, D; Miceli, A; Pace, S; Patruno, M; Gujiarro Ponce, P; et al.
Abstract: Study question: Can outcomes of transnational egg donation treatments, which involves the shipping of cryopreserved partner semen, be affected by advanced paternal age? Summary answer: Male age does not affect percentage of motile spermatozoa after thawing. Advanced paternal age does not affect IVF laboratory outcomes of transnational egg donation treatments What is known already: Studies on advanced paternal age are limited and a clear definition of advanced paternal age is still missing. The separation between advanced paternal and maternal age effects is hampered by the collinearity of maternal age with paternal age, since older males are often associated with older women. Many studies have focused on egg donation treatments, to overcome this problem. However, these studies reported conflicting results, such as a putative effect of advanced paternal age on ICSI outcomes, while some others not. This study analyzes paternal age in transnational egg donation program, which involves the shipping of cryopreserved partner semen Study design, size, duration: A multicentric retrospective cohort study involving 101 couples and 327 blastocysts was performed from June 2018 up to December 2021. Two Italian IVF centers involved a Spanish center to perform a transnational fresh oocyte donation program. The aim of the study was to analyze the putative effect of male age on (i) semen parameters, (ii) fertilization rate and (iii) blastocyst rate. Participants/materials, setting, methods: Donations of both male and female gametes were excluded. We performed sperm cryopreservation of the male partner of the recruited couples. Frozen samples were shipped with a authorized courier, which certified the safety of the whole procedure. The day of donor's egg retrieval, semen samples were thawed and ICSI was performed on fresh donated oocytes. Resulted blastocysts were vitrified and shipped to the centers where the frozen embryo transfers in the recipient patients were performed. Main results and the role of chance: The mean of male partners age was 42.6 ± 6.5 (min 26- max 63). Overall fertilization rate was 81.6% (686/840), and blastocyst rate was 47.6% (327/686). Male age was analyzed as a continuous variable and divided into five groups calculated for 5-year intervals. No differences in terms of fertilization rates nor blastocysts rates were found (85.3% and 43.7% for <35-years; 84.7% and 54.0% for 36-39-years; 79.7% and 44.2% for 40-44-years; 89.6 and 48.1% for 45-49-years; 74.5% and 56.5 for >50-years). Although advanced paternal age has been correlated to the decrease of most of sperm parameters, in the present study we found that only progressive rapid motility was significantly affected by advanced paternal age (coefficient -0.261, P = 0.009). To evaluate the predictive value of advanced paternal age and sperm parameters on fertilization and blastocysts formation, we performed a multiple linear regression analysis. We found that sperm parameters and male age in our sample are not predictive of the number of fertilized oocytes nor the number of obtained blastocysts. Importantly for the setting of the study, the percentage of progressive motile sperm at the thawing was not influenced by paternal age. Limitations, reasons for caution: The main limitation of the study is the small sample size, which might mask the paternal age effect on the sperm parameters, as the volume, which tend to decrease in the classes of age, but did not reached the statistical significance. The multicentric nature of the study represent a strength Wider implications of the findings: The discomfort for couples that need oocyte donation in countries where there is a low availability of egg donors is often underestimated. This study demonstrate that, independently of male age, the shipping of frozen sperm and the ICSI of freshly donated oocytes represent a valid option for these couples. Trial registration number: not applicable